Production of corn and forage soybeans for silage and partial marketing of the baby corn or ears crop. - Jiménez, Carlos (2006)
Theeffect of three different planting methods for soy and cornwas evaluated: a) every other row, b) four rows of each andc) mono-culture and three harvesting methods of themarketable crop: a) removal of 50% of baby corn (bloomingonset), b) removal of 50% of corn ears (milk stage) and c) noharvest. Each treatment had three replications. The cornvariety was HS-5G (Cristiani Burkard) and that of soybeanwas CIGRAS 10, a variety for grain and forage developed bythe Centro de Investigación en Granos y Semillas de laUniversidad de Costa Rica and successfully grown in the DryPacific Region of Costa Rica. Harvesting for silage wasperformed at the phenological stages of pre-indentation forcorn and R6 for soybean (formed seed in dough stage).Harvesting 50 % of baby corn resulted in $164.06 of grossincome, covering 44.23 % of total expenses for planting,growing, harvesting and ensiling in a clamp silo. However, adecrease from 5.99 to 4.77 tDM/ha was observed,representing a 20.3 % reduction. Ears harvest also reducedyield by 24.4 %, but allowed for an 89.45 % recover of theexpenses, equivalent to $331.75 of gross income. Removal ofthe ears is well justified, since it recovers almost all of thecosts; although there is a reduction in yield and most certainlyin digestible dry matter. If weather conditions had been morefavourable, a higher gross income could have been obtained,with money surplus and a free crop of silage.